2015
DOI: 10.3171/2015.1.focus14743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of convection-enhanced delivery of bevacizumab on survival of glioma-bearing animals

Abstract: OBJECT Bevacizumab (Avastin), an antibody to vascular endothelial growth factor (VEGF), alone or in combination with irinotecan (Camptosar [CPT-11]), is a promising treatment for recurrent glioblastoma. However, the intravenous (IV) administration of bevacizumab produces a number of systemic side effects, and the increase in survival it provides for patients with recurrent glioblastoma is still only a few months. Because bevacizumab is an antibody against VEGF, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…This result supports further developing CED by showing that current glioblastoma treatments could be more effective via CED. 80 Other studies published in 2015 assessed the efficacy of CED of agents used to systemically treat glioblastoma such as irinotecan, carboplatin, and cetuximab delivered via nanoparticles and liposomes to allow gradual release after CED. 1,26,43 These preclinical studies have improved CED techniques and identified agents to infuse via CED, information that has given rise to the multiple clinical trials in patients described below.…”
Section: Resultsmentioning
confidence: 99%
“…This result supports further developing CED by showing that current glioblastoma treatments could be more effective via CED. 80 Other studies published in 2015 assessed the efficacy of CED of agents used to systemically treat glioblastoma such as irinotecan, carboplatin, and cetuximab delivered via nanoparticles and liposomes to allow gradual release after CED. 1,26,43 These preclinical studies have improved CED techniques and identified agents to infuse via CED, information that has given rise to the multiple clinical trials in patients described below.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically CED can maximize the brain concentration of the treatment drug with minimal systemic exposure and toxicity [15]. It has been found that the concentration of the drug injected into the brain by CED can reach more than a thousand times that following traditional drug administration, and the region in which the drug is applied can be relatively vast [16][17][18][19]. However, the use of CED has been limited in clinical practice because of the difficulty in monitoring and controlling the concentration and distribution of the injected drugs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Direct drug delivery is one of several methods that may be used to circumvent this restriction, but limitations in the ability to monitor drugs distributed in the ISF system have prevent this technique from being reliable and reproducible. Moreover, the parameters required for direct local drug administration (e.g., delivery pressure, time, and frequency) are mostly acquired through experience [4].…”
mentioning
confidence: 99%
“…A phase III trial where CED was used to administrate interleukin-13 bound to Pseudomonas exotoxin to GBM patients did not show a significant improvement compared to Gliadel wafers [409]. Nevertheless, other preclinical studies have shown promising results [410], and continuous efforts have been made to improve the efficiency of CED, including works in catheter technology and optimal positioning [406]. Recently, a chronic CED administration system was used to infuse the topoisomerase inhibitor topotecan in a pig model for up to 32 days without toxicity [411].…”
Section: Local Delivery: Polymeric Drug Delivery Systems and Convectimentioning
confidence: 99%